Successful Management of Patient with Treatment Resistant Schizophrenia and Swyer–James–Macleod Syndrome with Clozapine - Parmar, Arpit (Indian J Psychol Med, 2016)
Swyer–James–Macleod syndrome (SJMS) is a rare disorder characterized by infective bronchiolitis. It typically presents with a history of recurrent chest infections during childhood. Cardinal sign of the disease includes the hyperlucency of the lung fields. Till date, only a few cases have been reported of this syndrome. We report a very unusual case of SJMS along with comorbid schizophrenia in a 20-year-old female and the successful management using clozapine.